TINDAKAN KONSUMTIF DALAM AKTIVITAS BELANJA ONLINE MAHASISWA DI FAKULTAS ILMU SOSIAL DAN POLITIK UNIVERSITAS SAM RATULANGI MANADO - Elnino, Samuel Raydean; Lesawengen, Lisbeth; Lasut, Jouke J. (Universitas Sam Ratulangi, 2020)
The increasement internet development causes the changes that influences the society’s life, mainly for the big cities society, such as Manado, North Sulawesi Province, one of the changes is the shopping place especially for the students. They go shopping to the conventional shop and online shop either. It makes the conventional markets promote their goods through the online shops. The changes of consumers mainly the students causes one of the supporting changes. They no longer consumes the goods and services at the conventional market but using online shops. Unfortunately, the students go shopping not because of their needs but only for their desire and lifestyle so it causes the consumerism life style which is known as wasteful. This research uses the qualitative method with the descriptive approach that useful for giving the the facts and datas about the students shopping online activity, then the datas will be critically analyzed by the theory of society's consume by Jean Baudrillard and the theory of needs by Abraham Maslow therefore the deeper analization about the purpose of students online shopping activity will be created. Based on the researches result, it is found that there are three categories of the students online shopping activity: 1. Based on their needs 2. Get influenced by other things such as: promotions of discounts, cashback, giveaway, bonus, or the certain gifts from the seller or the advertisements in electronics media or the social media, the recommendation from others also, and 3. Because of the lifestyle Keywords: Consumptive Actions, Online Shopping, Student